Gas-Phase and Aqueous Photocatalytic Oxidation of Methylamine: The Reaction Pathways - Anna Kachina; Sergei Preis; German Charles Lluellas; Juha Kallas (International Journal of Photoenergy)
Photocatalytic oxidation (PCO) of methylamine (MA) on titanium dioxide in aqueous and gaseous phases was studied. A simple batch glass reactor for aqueous PCO and an annular continuous flow reactor for the gas-phase PCO were used. Maximum aqueous PCO efficiency was achieved in alkaline media. Two mechanisms of aqueous PCO—decomposition to formate and ammonia, and oxidation of organic nitrogen directly to nitrite—lead ultimately to CO2, water, ammonia, and nitrate: formate and nitrite were observed as intermediates. A part of the ammonia formed in the reaction was oxidized to nitrite and nitrate. Volatile PCO products of MA included ammonia, nitrogen dioxide (NO2), nitrous oxide (N2O), carbon dioxide, and water. Thermal catalytic oxidation (TCO) resulted in the formation of ammonia, hydrogen cyanide, carbon monoxide, carbon dioxide, and water. The gas-phase PCO kinetics is described by the monomolecular Langmuir-Hinshelwood model. No deactivation of TiO2 catalyst was observed.